Open Secrets: Methods and Archives in Chinese Canadian Histories - Ng, Melanie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
From the late nineteenth to the mid-twentieth century, anti-Chinese immigration laws structured the restriction and exclusion of Chinese migrants in Canada. However, Chinese strategies used to circumvent these laws were open secrets. This article examines the strategy of paper family migration to investigate the following ethical and methodological dilemmas: What is a secret? How might we study secrets without exposing community knowledge? How do we find archival traces of people who do not wish to be found? Chinese migrants created paper families when they purchased the identification papers, and performed the identity, of a person who was legally admissible to the country, a process I call passing. My contribution to this forum takes paper families as an opportunity to consider the role of secrecy in both Chinese migrants’ passing and efforts by immigration agents to regulate them. I argue that secrecy conditioned knowledge production for Chinese paper families and state officials. Rather than approach secrets as hidden knowledge, I understand secrets as a particular kind of knowledge. Doing so not only avoids the risks of exposing passers but offers a method for studying secrecy that foregrounds understandings of why these secrets were produced, how they were kept, and what they achieved.